Dust models for the extinction of Type IIn supernova SN 2010jl. Issue 2 (31st January 2022) - Li, Jun; Gao, Jian; Jiang, Biwei; Lin, Zesen
ABSTRACT: The unusual extinction curves of SN 2010jl provide an excellent opportunity to investigate the properties of dust formed by core-collapse supernovae. By using a series of dust models with different compositions and grain size distributions, we fit the extinction curves of SN 2010jl and find that a silicate–graphite mixture dust model characterized by exponentially cut-off power-law size distributions can well reproduce its unusual extinction curves. The best-fitting results show that the extinctions derived from the dust models are consistent with the observed values at all epochs. However, the total-to-selective extinction ratio RV is ∼2.8–3.1, which is significantly smaller than the value of RV ≈ 6.4 derived by Gall et al. The best-fitting models indicate that the dust grains around SN 2010jl are possibly composed of small-sized astronomical silicate grains and micron-sized graphite grains. In addition, by fitting the optical to mid-infrared spectral energy distribution, we find that the dust mass around SN 2010jl increases with time, up to $0.005\, M_{\odot }$ around 1300 d after peak brightness, which is consistent with previous estimates (Gall et al.; Sarangi et al.).